LITERATURE REVIEW TEKNIK PEMERIKSAAN RADIOLOGI MOLAR PADA KLINIS IMPAKSI DENGAN MENGGUNAKAN MULTIMODALITAS - Sri Hartati; Maya Puspitasari (JRI (Jurnal Radiografer Indonesia), 2022)
Background: Dental tooth impaction is a state of latent or not erupted or partly erupted after a normal eruption time, Impacted teeth can be estimated clinically and can be confirmed by radiographic examination. Methods: This study aims to determine the radiological examination technique of molars in clinical impaction using multimodality based on a literature review. This research is library research. The data collection method used in this research is the method of theory study/literature study/library study. Results: Based on studies from several journal literatures, there are several radiological techniques that can be performed in clinical molar impaction such as periapical intraoral radiography, panoramic, CBCT, and MRI. On periapical intraoral radiology, the molars and panoramic radiographs do not clearly show molars impacted with the mandibular canal and inferior alveolar nerve, but on CBCT and MRI they are clearly visible using existing sequences and techniques. However, with the use of CBCT modalities, the radiation obtained is very high. Therefore, the use of a radiation-free MRI modality is a highly invasive examination for clinically impacted molars. Conclusions: With a variety of available modalities for clinically impacted molars, it is recommended to use intraoral periapical and panoramic if the case or clinical can still be seen in that modality, if not or less visible in that modality with certain cases or clinical can be used CBCT examination but do not overuse of these modalities because the ionizing radiation emitted is very high/dangerous. It is suggested that the use of dental MRI modalities could be increased in an important step towards being radiation free, improving intervention planning and thereby increasing the overall patient benefit.